Towards a Knowledge Society – State Contribution in Higher Education (Journal of Advanced Research in Journalism & Mass Communication, 2018)
With universities becoming a seat of power and the principal driver of change in any society, it has become imperative for the state to play an active role in the growth and proliferation of institutions of higher education. No more is the need greater than in countries like India that have long borne the ill-effects of improper planning and negligence of human resource, especially in the education sector. The state machinery in India has thankfully begun to recognize the fallacy within its system and put the wheels in motion towards bringing in the much-needed change. Educational institutions too on their part are demanding a rightful place in the scheme of things with most universities vying for a coveted place in the world university ranking list. State intervention is critical now if the planning and strategizing from both fronts has to bear fruition. This paper attempts to explore the issue of state initiatives in the field of higher education in India. How to cite this article: Naresh S. Towards a Knowledge Society – State Contribution in Higher Education. J Adv Res Jour Mass Comm 2018; 5(3): 22-25. DOI: https://doi.org/10.24321/2395.3810.201810